Antischistosomal activity of artemisinin derivatives in vivo and in patients. (August 2016) - Saeed, Mohamed E.M.; Krishna, Sanjeev; Greten, Henry Johannes; Kremsner, Peter G.; Efferth, Thomas
Graphical abstract: Abstract: Schistosomiasis is a helminthic disease affecting more than 200 million people in the tropics as well as returning travellers. Treatment mainly relies on a single drug, praziquantel. Praziquantel cannot kill developing schistosomula resulting in frequent treatment failures and re-infections. Monotherapy also favors the selection for resistance. New drugs are therefore urgently needed. The activity of the semi-synthetic artemisinin derivatives artemether, artesunate and arteether is not restricted to malaria. We reviewed their anti-schistosomal activity in vivo and in patients by searching the PubMed database for publications since 1983 with the search terms "artemisinin" and " Schistosoma ". Reports on in vivo studies in animals and clinical trials in human beings were selected. S. mansoni, S. japonicum, and S. haematobium have been tested in mice, rabbits, hamsters, and dogs. These artemisinin derivatives strongly reduced total worm rates with stronger reduction rates for female worms than for males. The drugs also reduced egg burden and egg-caused granulomata in the host liver. Artemisinin-type drugs induced oxidative and metabolic stress leading to morphological damage and decreased fertility of the parasites. Although artemether and artesunate have been investigated in numerous clinical trials, the poor quality of many has led to inconsistent results and has not provided convincing evidence on the therapeutic value against schistosomiasis. Despite these methodological concerns, clinical trials may indicate anti-schistosomal activity in patients. Convincing clinical trials providing unambiguous evidence are now needed. Furthermore, suitable treatment protocols for combination therapy to prevent/treat praziquantel-resistant Schistosoma strains should be investigated.